2017
DOI: 10.1515/prolas-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity and Contrast Sensitivity Depending from Keratoconus Apex Position

Abstract: Various studies have demonstrated that patients with keratoconus have significant loss of contrast sensitivity while its value varies in different studies. None of these studies has analysed reduced contrast sensitivity depending on the position of apex of corneal conus. Visual acuity and contrast sensitivity were evaluated for patients with keratoconus using the FrACT software. Contrast sensitivity was assessed at the following frequencies: 1, 3, 5, 7, 9, 11, 13, and 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Research on contrast sensitivity changes in keratoconus is limited. Some authors have confirmed that contrast sensitivity is reduced in keratoconus subjects compared to normal controls 14 , 17 , 18 . Likewise, contrast sensitivity at medium and high frequencies was shown to be reduced in keratoconus subjects before visual acuity decreases 19 .…”
Section: Introductionmentioning
confidence: 90%
“…Research on contrast sensitivity changes in keratoconus is limited. Some authors have confirmed that contrast sensitivity is reduced in keratoconus subjects compared to normal controls 14 , 17 , 18 . Likewise, contrast sensitivity at medium and high frequencies was shown to be reduced in keratoconus subjects before visual acuity decreases 19 .…”
Section: Introductionmentioning
confidence: 90%
“…Keratokonusa pacientiem ir statistiski nozīmīgi samazināta kontrastjutība vidējās un augstās kontrastjutības telpiskajās frekvencēs (Liduma & Krumina, 2017), gan atkarībā no keratokonusa stadijas, gan no keratokonusa virsotnes atrašanās vietas. Tas liecina, ka keratokonusa pacientiem jābūt atšķirībām augstākās kārtas aberācijās.…”
Section: Diskusijaunclassified